A integração entre contabilidade e fiscalização tributária para o fortalecimento da governança pública - Marcos Vinicius Montalvão da Silva (Revista ft, 2026)
The integration of public sector accounting and tax auditing has gained relevance in view of the digitalization of financial administration, the need for greater transparency, and the changes arising from the reform of consumption taxation. Within this context, the study aimed to analyze how the coordination of accounting records, tax systems, and control activities contributes to strengthening public governance, considering efficient revenue collection, fiscal responsibility, and legal certainty. A narrative literature review was conducted using a qualitative and descriptive-analytical approach, based on searches of scientific databases, specialized journals, and institutional websites. Articles published between 2020 and 2026 were selected, with priority given to Brazilian research, together with relevant accounting, financial, and tax legislation. Reviews, dissertations, theses, conference papers, and publications unrelated to the research subject were excluded. The analysis indicated that reliable, timely, and reconcilable records support internal control, accountability, and the use of economic information for tax purposes. However, technological fragmentation, dependence on service providers, disparities in municipal technical capacity, and deficiencies in taxpayer registries reduce the reliability of financial statements and constrain tax auditing capacity. The discussion revealed that digitalization alone does not ensure information quality, since system effectiveness depends on standardization, interoperability, data governance, and institutional oversight. Accounting manipulation and fiscal decisions disconnected from planning were also found to undermine administrative predictability. It was concluded that accounting-tax integration can improve revenue collection and public accountability, provided that it is accompanied by consistent controls, professional qualification, verifiable transparency, and uniform application of regulations across all levels of government within the Brazilian Federation.